Peningkatan Hasil belajar Pendidikan Agama Hindu dan Budi Pekerti Melalui Penerapan Asesmen Portofolio - Ida Ayu Made Supadmi (Jayapangus Press, 2019)
In learning Hinduism Education and Characteristics often found learning outcomes are not optimal. Not optimal learning outcomes obtained by students problems and find alternative ways or efforts that can be done to improve student learning outcomes in subjects of Hindu Religion and Character Education. The application of portfolio assessment in the learning of Hinduism, makes the learning process more varied and not saturating. Conditions like this will foster the motivation of students to learn more about the material of Hinduism Education. With the growth of student motivation will affect the process and way of learning in Hinduism Education and Characteristics so that they can improve their learning outcomes more optimally.